Republic of North Macedonia : Action Plan for Recovery of Growth and Jobs - World Bank (World Bank, Washington, DC, 2020)
North Macedonia has made considerable progress in recent decades, moving from lower-middle to upper-middle income status, and from a planned to a functional market economy. Despite these reforms, the domestic economy still lacks the needed dynamism to move into higher-income status, as evidenced by a declining and low productivity challenge. Compounding this challenge, the economy also faces a low employment and skills challenge. To address its productivity challenge North Macedonia will need to continue to attract FDI and engage in an ambitious strategic regulatory and firm-level reform agenda. North Macedonia will need, as well, to continue supporting the development of a skilled and well-trained labor force that can match the upcoming demands of the private sector.